An Isoparametric Finite Element Method for Reissner-Mindlin Plate Problem on Curved Domain (Advances in Applied Mathematics and Mechanics, 2024)
In this paper, we present an application of the isoparametric finite elementfor the Reissner-Mindlin plate problem on bounded domain with curved boundary.The discrete scheme is established by isoparametric quadratic triangular finite elementcombined with a numerical quadrature. Under the certain numerical quadrature, weprove the existence and uniqueness of the numerical solutions and the error estimatesof optimal order in $H^1$-norm are given in details with the help of rigorous analysis.Finally, a numerical example is provided to verify the theoretical results.